2012
DOI: 10.5173/ceju.2012.03.art9
|View full text |Cite
|
Sign up to set email alerts
|

LAPAROSCOPY Fertility preservation in cases of laparoscopic treatment of seminal vesicle cysts

Abstract: Seminal vesicle cysts can cause sub- or infertility. Minimally invasive techniques have the advantage of preserving the vas deferens by the treatment of symptomatic cases. After reviewing the published articles, only a few of them presented data on fertility before and after surgery. The authors now report the successful treatment of two patients with seminal vesicle cysts, in which laparoscopic cyst removal resolved the symptoms, preserving fertility and erectile function. Due to the rarity of seminal vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Nowadays, laparoscopic and robotic techniques have replaced the open surgical approach 17 18. Removal of the seminal vesicle cysts can resolve symptoms while preserving fertility and erectile function 19. As the condition is benign, periodic clinical follow-up is sufficient and imaging is reserved for those patients who become symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, laparoscopic and robotic techniques have replaced the open surgical approach 17 18. Removal of the seminal vesicle cysts can resolve symptoms while preserving fertility and erectile function 19. As the condition is benign, periodic clinical follow-up is sufficient and imaging is reserved for those patients who become symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…However, several previous researchers hold different opinions. Benyo et al , 17 after studying two relevant cases of their own and reviewing seven similar cases in the literature, claimed that TLU could also enhance total motile sperm count and preserve fertility of SVC patients. Valla et al 18 reported that TLU was able to preserve fertility of an infant who was confirmed with SVC.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of fertility in patients presenting with symptomatic seminal vesicle cyst has been mostly overlooked with only a few reports published. Benyó et al [19] reported on 2 patients treated with laparoscopic nephroureterectomy and seminal vesicle cyst excision who performed sperm analysis before and after surgery. In 1 patient, the sperm count showed asthenozoospermia, which was corrected in a second sperm analysis 18 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It is considerable to perform sperm analysis in these patients while employing several intraoperative techniques such as limiting the use of bipolar coagulation, careful dissection, and the administration of intravesicle methylene blue for the preservation of the vas deferens during operation [19] . In this series of patients, we did not perform sperm analysis mainly because the patient was constrained by religious causes and refused to appear for examination; however, during the operations a meticulous dissection was performed with attention to the preservation of the vas.…”
Section: Discussionmentioning
confidence: 99%